The Depending on Meaning between Performance and Guidance - Bani Issa, Ahmed; Al Qiyam, Ismail; Dawagreh, Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify one of the widespread phenomena in the Arabic language- the phenomenon of inferring on meaning - and to study the philosophy of violation in it; in gender, number, and syntax. Methods: The study adopts the descriptive analytical approach to monitor examples of inferring on meaning and its applications in the Arabic language and its various uses, and to analyze them with the help of the opinions of old and modern linguists. Results: The study revealed the prevalence of the phenomenon of inferring on meaning in the Arabic language, as it is considered an entry to interpretation for many of the cases in which Morphological retraction occurs, and with this interpretation, the irregular is subjected to the rule, and this is the philosophy of inferring on meaning in general. Conclusion: The study concluded that inferring on meaning is a linguistic phenomenon that lies between the speaker’s performance and the grammarian’s analysis. The speaker’s reference point is the capacity of the language on the one hand, and the abstract mental structure in general on the other hand. The speaker has several possibilities to transfer what is in his mind to words, as the meaning may call for its antonym, or synonym, and the result is to infer this to that and that to another. So, the grammarian is keen to control the linguistic phenomenon, not in terms of usage, but by trying to subject it to uniformity.